2001
DOI: 10.1002/jmri.1168
|View full text |Cite
|
Sign up to set email alerts
|

In vivo studies of Gd‐DTPA‐monoclonal antibody and gd‐porphyrins: Potential magnetic resonance imaging contrast agents for melanoma

Abstract: New tumor-specific contrast agents for clinical imaging and therapy for cancer are required. To this end Gd-H (Gd-hematoporphyrin), Gd-TCP (Gd-tetra-carboranylmethoxyphenyl-porphyrin), Gd-DTPA-WM53, and Gd-DTPA-9.2.27 were synthesized and administered by systemic injection to nude mice with human melanoma (MM-138) xenografts. The biodistribution T 1 relaxation times and magnetic resonance (MR) image signal enhancement of the contrast agents are presented for the first time and compared for each group of five m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(55 citation statements)
references
References 23 publications
2
53
0
Order By: Relevance
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…There is a great deal of interest in enhancing the utility of these tools in medicine and research through the development of molecularly-targeted MRI contrast agents. One example might be a chimeric molecule comprised of a contrast agent tethered to a molecule capable of binding to a specific protein or other biomolecular target with high affinity and specificity [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. For example, we previously reported that a peptide selected from a phage display library to bind the yeast Gal80 protein can be linked to GdDOTA to create a reagent capable of imaging Gal80 protein in vitro [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…T 1 -weighted MR imaging procedures were performed at different time intervals after injection. For the confirmation of the data obtained by MR imaging, a digestive acid method was done followed by sacrificing some mice and removing critical organs using ICP-AES (inductive coupled plasma atomic emission spectroscopy) method described previously [17].…”
Section: Tumor Mr Imagingmentioning
confidence: 99%
“…One of the targets is breast specific membrane antigen, MUC-1, a high molecular weight transmembrane glycoprotein antigen [15][16][17][18][19]. Additionally, tumor marker antigen MUC-1 is a proposed molecular target for a novel imaging or therapy for breast cancer [20].…”
Section: Introductionmentioning
confidence: 99%
“…It was recently shown that a porphyrin-based MRI molecular imaging agent, Mn-(DPA-C 2 ) 2 -TPPS 3 , effectively penetrates cells and persistently stains living brain tissue in intracranially injected rats. Due to cromogenicity, its distribution can also be observed by histology (Chen, 1984;Shahbazi-Gahrouei, 2001). Porphyrin-based complexes were also identified as necrosis-avid contrast agents (NACAs) for noninvasive MRI identification of acute myocardial infarction, assessment of tissue or organ viability, and therapeutic evaluation after interventional therapies (Ni, 2008).…”
Section: Contrast Media For Mrimentioning
confidence: 99%